A influência das variáveis do lixamento tubular na qualidade das peças de Eucalyptus grandis - Varanda, Luciano Donizeti; Alves, Manoel Cleber de Sampaio [UNESP]; Gonçalves, Marcos Tadeu Tibúrcio; Frezzatti, Luiz Fernando (My University, 2010)
In 2010, the Brazilian forest sector is represented by about 30,000 companies producing US$ 21 billion annually and account for approximately 5% of the gross domestic product (GDP) in the country. The sanding process is highly demanded in various stages of industrialization of the wood, when there is a need for a better quality surface finishing. The objective of this work was to analyze the influence of cutting speed and sandpaper granulometry on both the surface finishing of pieces of Eucalyptus grandis processed through tubular sanding and on the sanding efforts (force and power of sanding). Four cutting speeds were used (19.5, 22.7, 26 and 28.1 m/s), one advance speed (16 m/min) and three sets of sandpaper (80-100, 80-120 and 100-120) being one for chipping and another for finishing, respectively. A central data acquisition system was set up to capture the variables (cutting power, acoustic emission and vibration) in real time. The cutting force was obtained indirectly, through a frequency inverter. The roughness of the parts was measured by a roughness meter before and after sanding. The highest cutting speed used (28.1 m/s) consumed more power and generated more acoustic emission among the four speeds tested. Regarding the vibration, the lower cutting speed (19.5 m/ s) generated the highest vibration in the sander machine. It is concluded that the range of 100-120 sandpapers resulted in values of average roughness (Ra) lower than the other sets of sandpaper used, as it resulted in better surface finishing.

Em 2010, o setor florestal brasileiro é representado por cerca de 30 mil empresas que produzem US$ 21 bilhões anuais e são responsáveis por aproximadamente 5% do produto interno bruto (PIB) do país. O processo de lixamento é muito requisitado em diversas etapas da industrialização da madeira, onde há a necessidade de um acabamento superficial de melhor qualidade. Este trabalho foi realizado com o objetivo de analisar a influência da velocidade de corte e da granulometria das lixas tanto no acabamento superficial de peças de Eucalyptus grandis processadas por meio do lixamento tubular quanto nos esforços de lixamento (força e potência de lixamento). Utilizaram-se quatro velocidades de corte (19,5; 22,7; 26 e 28,1 m/s), uma velocidade de avanço (16 m/min) e três conjuntos de lixas (80-100, 80-120 e 100-120), sendo uma de desbaste e outra de acabamento, respectivamente. Uma central de aquisição de dados foi montada para a captação das variáveis (potência de corte, emissão acústica e vibração) em tempo real. A força de corte foi obtida de maneira indireta, por meio de um inversor de frequência. A rugosidade das peças foi medida por um rugosímetro antes e depois do lixamento. A maior velocidade de corte utilizada (28,1 m/s) consumiu maior potência e gerou maior emissão acústica dentre as quatro velocidades analisadas. Quanto à vibração, a menor velocidade de corte (19,5 m/s) gerou maior vibração na lixadeira. Conclui-se que o conjunto de lixas 100-120 resultou em valores de rugosidade média (Ra) inferiores aos demais conjuntos de lixas utilizados, ou seja, resultou em melhor acabamento superficial.
Keywords: Wood sanding; Eucalyptus grandis; Data acquisition; Machining; Roughness; Lixamento de madeira; Eucalyptus grandis; Aquisição de dados; Usinagem; Rugosidade